A redox‐additive electrolyte for cobalt‐manganese‐layered double hydroxides‐based asymmetric supercapacitor. (6th September 2022) - Vijaya, Subbiah; Sharma, Piyush; Aljafari, Belqasem; Anandan, Sambandam
Summary: A cobalt‐manganese‐layered double hydroxide (CoMn‐LDH), the extremely desired electrode material in supercapacitors, has been synthesized via a one‐step hydrothermal technique. The XRD analysis confirmed the formation of the CoMn‐LDH. The nanorod‐shaped surface morphology is revealed from the scanning electron microscopy and transmission electron microscopy analysis. The asymmetric supercapacitor has been constructed by employing activated carbon as anode material and CoMn‐LDH as cathode material. The electrodes have been investigated in the mixed electrolyte comprised of potassium hydroxide and potassium ferricyanide. The fabricated supercapacitor with the two‐electrode system delivers the highest specific capacitance of 30 F/g at 1 mA along with the highest energy and power density of 6 Wh/kg and 1400 W/kg. Furthermore, the electrodes demonstrate high capacity retention of 81.25% at a high current density of 5 mA after 1000 cycles. Abstract : A cobalt‐manganese‐layered double hydroxide‐based asymmetric supercapacitor in the presence of redox‐additive electrolytes delivers the highest specific capacitance of 30 F/g at a current density of 1 mA.